DRUG USE PATTERN AND IMPACT OF CLINICAL PHARMACIST INTERVENTION IN PRESCRIBING DRUGS FOR PATIENTS WITH ACUTE KIDNEY INJURY AT THONG NHAT HOSPITAL - Nguyen, Nhi Truc Y; Nguyen, Bach; Pham, Hien Thi Thu; Tran, Mai Thi Phuong; Thi Huong Bui, Quynh (Journal of Health and Aging, 2025)
Medication management in patients with acute kidney injury (AKI) poses numerous challenges due to the rapid fluctuations in renal function over a short period. This necessitates frequent reassessment of drug indications and dosages to ensure both treatment efficacy and patient safety. This study aimed to investigate the drug use characteristics and evaluate the effectiveness of clinical pharmacist interventions in prescribing medications for patients with AKI; A before-and-after study was conducted on inpatients diagnosed with AKI at Thong Nhat Hospital, Vietnam, during the pre-intervention period (from February 2022 to August 2022) and the intervention period (from September 2022 to March 2023). Clinical pharmacist interventions included reviewing prescriptions and providing guidance on dose adjustments for patients with AKI. Prescriptions were considered appropriate if the indications and dosages complied with drug usage guidelines and the Vietnamese National Drug Formulary. The effectiveness of the intervention was evaluated by comparing the appropriateness of prescribing between the two study periods; A total of 97 patients in the pre-intervention period and 94 patients in the intervention period were included. The proportion of patients receiving at least one drug potentially impairing kidney function in both periods was 33.5%, while 90.6% of patients were prescribed at least one drug that required dose adjustment or discontinuation in cases of renal impairment. The proportion of appropriately dosed prescriptions was higher in the intervention period compared to the pre-intervention period (94.7% vs. 84.5%, p = 0.022). However, the overall rate of appropriate prescribing did not differ significantly between the two periods (79.8% vs. 71.1%, p = 0.165); The rate of appropriate prescribing for AKI patients was relatively high. Clinical pharmacist interventions contributed to improving the appropriateness of drug dosing.